Assessment of 2,4-difluoroaniline Aquatic Toxicity Using A Zebrafish (Danio rerio) Model - Moșneang, Crina Laura; Grozea, Adrian; Oprescu, Ion; Dumitrescu, Eugenia; Muselin, Florin; Gál, Dénes; Cristina, Romeo T. (The Thai Journal of Veterinary Medicine, 2014)
Bio-monitoring, in the control strategies for pollution, has several advantages over other tests in aquatic organisms. Bio-effects may link the bioavailability of the compounds of interest with their concentration at target organs and intrinsic toxicity. Potential harmful effects of 2,4-difluoroaniline (DFA), on a 96-hour acute static test, on adult zebrafish (Danio rerio) were followed. According to OECD 203: Fish Acute Toxicity Test, LC50 was determined using 70 adult zebrafish AB strain and 14 zebrafish as control group, to evaluate the effects and action at different concentrations of DFA. Obtained data were analyzed using Minitab Statistical Software as Goodness-of-Fit correlation tests. Logarithmic value obtained for LC50 was of 2.30311, which corresponded to LC50 of 200.96 mg/L. Results from the performed work reinforce the idea of the zebrafish adults as simple and easy reproducible model organisms in ecotoxicology. Although there are more comprehensive tests available, this particular one is both rapid and relatively cheap. The results obtained for LC50, in our opinion, are useful and applicable to a large number of substances, especially in field conditions when overall effectiveness is more important than meticulousness of the method.